Mr 40, 000 human colonic epithelial protein expression in colonic mucosa and presence of circulating anti-Mr 40, 000 antibodies in cotton top tamarins with spontaneous colitis. Issue 1 (January 1992) - Das, K M; Vecchi, M; Squillante, L; Dasgupta, A; Henke, M; Clapp, N
Abstract : Saguinus oedipus, Callithrix jacchus, and Saguinus fuscicollis are three species of New World monkeys which develop a form of colitis that is similar to human ulcerative colitis. Only S oedipus, however, develop colon cancer. We examined intestinal tissues from these animals for the presence of an antigen cross reacting to the Mr 40, 000 human colonic epithelial protein that acts as an autoantigen in ulcerative colitis. Using an anti-Mr 40, 000 monoclonal antibody (7E12H12, IgM isotype), by an immunoperoxidase assay we showed that all colon specimens from S oedipus reacted with 7E12H12; however, the colonic tissue from C jacchus and S fuscicollis did not. In immunotransblot analysis eluted IgG antibody bound to human ulcerative colitis colon (CCA-IgG) reacted with Mr 40, 000 protein(s) present in the extracts of colon from S oedipus animals and humans. Small intestinal tissue reacted neither with 7E12H12 nor with CCA-IgG. In S oedipus, the Mr 40, 000 protein was localised exclusively to colonic epithelial cells. Preincubation of seven S oedipus colon specimens with eight of 10 sera from animals with acute or chronic colitis and 0 of four sera from animals without colitis almost completely inhibited the binding of 7E12H12 to the colonic epithelium. Four of these 10 sera inhibited the binding of 7E12H12 to the autologous colon. These results show the presence of circulating autoantibodies in S oedipus with colitis against an epitope(s) on Mr 40, 000 protein shared by human and S oedipus colon.